Pseudomonas aeruginosa in Bronchiectasis - Fernández-Barat, Laia; Alcaraz-Serrano, Victoria; Amaro, Rosanel; Torres, Antoni (Seminars in Respiratory and Critical Care Medicine, 2021)
Pseudomonas aeruginosa (PA) in patients with bronchiectasis (BE) is associated with a poor outcome and quality of life, and its presence is considered a marker of disease severity. This opportunistic pathogen is known for its ability to produce biofilms on biotic or abiotic surfaces and to survive environmental stress exerted by antimicrobials, inflammation, and nutrient or oxygen depletion. The presence of PA biofilms has been linked to chronic respiratory infection in cystic fibrosis but not in BE. There is considerable inconsistency in the reported infection/eradication rates of PA and chronic PA. In addition, inadequate antimicrobial treatment may potentiate the progression from intermittent to chronic infection and also the emergence of antibiotic resistance. A better comprehension of the pathophysiology of PA infections and its implications for BE is urgently needed. This can drive improvements in diagnostic accuracy, can move us toward a new consensus definition of chronic infection, can better define the follow-up of patients at risk of PA, and can achieve more successful eradication rates. In addition, the new technological advances regarding molecular diagnostics, -omics, and biomarkers require us to reconsider our traditional concepts.
Keywords: bronchiectasis; Pseudomonas aeruginosa; biofilm; exacerbation; microbiome